Developing Android-Based Math Comic with Gamification Based on Mathematics Literacy - Fahmi, Syariful; Triyoga, Arilia; Priwantoro, Soffi Widyanesti; Nur Muallifah, Azizah; Purwadi, Joko; Bueraheng, Surairee (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This research is intended to develop a media of comic math learning based on android and mathematics literacy for the materials of linear equations system in two variables. This study is a research and development by using ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instruments are validation sheet, students’ response sheet and students' and teachers' interview guideline. The subjects of research are 27 students of grade VIII Sornsasana Sasanupathum School. The object of research is media of Math Comic for the material of linear equations system in two variables. Technique of data collection in the research was questionnaire distribution and interview, meanwhile the researcher analyzed the questionnaire and interview result data quantitatively by changing the qualitative data to be quantitative data to find out the appropriateness of math comic media. The assessment results in the research of math comic media were achieved by the assessment done by content expert with